Carbon-supported multimetallic electrocatalysts and their molten salt electrochemical preparation and application in OER / ORR
By using carbon felt or carbon cloth to wrap polymetallic organic complexes in the preparation of electrocatalytic materials, combined with molten salt electrolysis and calcination treatment, the problems of high-entropy nanoalloy composition and structural regulation and nanopowder preparation are solved, and excellent oxygen electrocatalytic performance and cell cycle stability are achieved.
Patent Information
- Application Number
- CN202510097734.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The prior art is difficult to accurately regulate the composition and structure of high-entropy nano alloys, and it is difficult to prepare nanopowder carbon-supported alloy nanostructured electrocatalytic materials for traditional molten salt electrochemical methods.
Carbon felt or carbon cloth is used to wrap polymetallic organic complex powder into a cathode, combined with molten salt electrolysis, acid treatment and subsequent calcination treatment, the strong current reduction of various transition metals in molten salt and homogenization and dispersion of carbon materials are achieved, and carbon-loaded polymetallic electrocatalytic materials with controllable structure are prepared.
The problem of phase separation of polymetal alloys was solved, and homogenized alloy nanoparticles were obtained, which significantly improved the oxygen electrocatalytic performance of the material and the cycle stability of the battery.
Smart Images

Figure CN119530893B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrode materials, and in particular relates to the field of OER and ORR catalytic materials. Background Art
[0002] Oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are key processes in renewable fuel cells and metal-air batteries, but their reaction kinetics are slow. The use of noble metal-based catalysts can improve the reaction kinetics, but their scarcity, high cost and easy deactivation limit their large-scale application. It is urgent to explore highly active non-noble metal catalysts.
[0003] Although some transition metals (Fe, Co, Ni, Cu, Mn, etc.) show catalytic activity for oxygen reduction reaction / oxygen evolution reaction, it is difficult to use directly due to its poor electrical conductivity, especially metal oxides with high catalytic activity. A better solution is based on the composite material obtained by combining transition metal with a conductive support, such as nano-carbon-loaded metal. The hybrid form of transition metals with nano-carbon as a carrier can obtain the advantages of the inherent properties of each component, such as electrochemical reactivity, mechanical stability, electrical / ionic conductivity, etc. In addition, nano-carbon materials can not only improve the conductivity of the catalyst, but also prevent the agglomeration of nanoparticles and improve dispersibility. Therefore, nano-carbon-loaded transition metals are used as effective bifunctional catalysts for oxygen electrocatalysis. For example, the Chinese patent literature with publication number CN 118699383 A discloses a method for preparing a nano high entropy alloy material, specifically recording a method for preparing an ORR / OER catalytic material by calcining a multi-metal organic complex, an active metal, and a molten salt mixture.
[0004] At present, the traditional smelting method is the main means of preparing nanoalloys, but this method can only obtain bulk alloys, so subsequent ball milling treatment is required to obtain powder materials. In addition, the preparation temperature of this method is high, and it is difficult to achieve precise control of the material scale and structure. If the wet chemical method commonly used in the field of nanomaterial preparation is adopted, the differences in the intrinsic properties of different metal precursors will lead to particularly prominent problems such as alloy phase separation, making it difficult to achieve homogenized alloy nanoparticle preparation. In summary, there are many challenges in the current preparation of multi-element alloys, especially high-entropy alloy nanostructures. It is difficult to accurately control the composition and structure of high-entropy nanoalloys, or the yield and scale still need to be improved. Therefore, it is crucial to develop a simple, effective, and structurally continuously controllable carbon-supported high-entropy metal catalyst preparation technology. Summary of the invention
[0005] In view of the problems existing in existing electrocatalytic materials, the first object of the present invention is to provide a method for preparing a carbon-supported multi-metal electrocatalytic material, aiming to prepare an alloyed nanomaterial with controllable structure and excellent oxygen electrocatalytic activity.
[0006] The second object of the present invention is to provide a carbon-supported multi-metal electrocatalytic material prepared by the preparation method and its application in ORR and / or OER catalysis.
[0007] The third object of the present invention is to provide a battery comprising the carbon-supported multi-metal electrocatalyst material.
[0008] Existing carbon-loaded metal electrocatalytic materials have complex synthesis methods and are difficult to accurately control the structural morphology. When using the molten salt thermal method, the carbon-loaded metal material is heated and cooled together with the molten salt. Due to the inconsistent melting points of various metals, it is easy for various metals to separate during the cooling process, making it difficult to obtain homogenized alloy nanoparticles. In response to these problems, the present invention attempts to prepare them using molten salt electrochemistry for the first time. However, earlier studies have shown that the traditional molten salt electrochemistry method usually requires the electrodes to be compacted, and it is difficult to obtain powdered carbon-loaded alloy nanostructured materials on the electrode side. In response to this problem, after in-depth research, the following solutions are provided:
[0009] A method for preparing a carbon-supported multi-metal electrocatalytic material, comprising wrapping a multi-metal organic complex with carbon felt or carbon cloth to form a cathode, connecting the cathode to an anode and performing electrolysis in a molten salt system, taking out the electrolysis product in the carbon felt or carbon cloth after the electrolysis is completed, and sequentially washing, acid washing and calcining the product to obtain a nano-scale carbon-supported multi-metal electrocatalytic material;
[0010] The multi-metal organic complex is a complex formed by a metal M source, a metal chelating agent and an organic complexing agent, and the metal M comprises three or more of Fe, Co, Ni, Cr, Mn, Cu, V, Mo, Ti, Au, Ag, Pt, Pd, Ru, Ir, Rh, W, La, Cd, Zr, Ga, In and Sn.
[0011] In view of the problem that the existing molten salt electrochemical technology is difficult to prepare nano-powder carbon-loaded alloy nanostructured electrocatalytic materials, the present invention innovatively uses carbon felt or carbon cloth to wrap multi-metal organic complex powder to form a cathode, and then cooperates with the molten salt electrolysis, acid treatment and subsequent calcination treatment. In this way, unexpected synergy can be achieved, so that multiple transition metals can be reduced by strong current in the liquid environment provided by the molten salt, and the carbon material can be well homogenized and dispersed under the strong solvation effect of the molten salt. After the electrolysis is completed, the electrode is promptly removed from the high-temperature molten salt to allow it to cool rapidly, which is beneficial to inhibiting the phase separation of the alloy. A higher specific surface area can be obtained while obtaining carbon-loaded multi-metal nanomaterials. Adjusting the composition and proportion of each metal and the electrolysis conditions can enable the carbon-loaded multi-metal electrocatalytic material to obtain the target adsorption energy, thereby obtaining the optimal oxygen electrocatalytic performance, especially taking into account excellent ORR and OER performance.
[0012] In the present invention, the multi-metal organic complex is preferably prepared by the following steps: pre-chelating the metal M source and the metal chelating agent, and then performing a complexing reaction with the organic complexing agent to obtain the multi-metal organic complex.
[0013] In the present invention, the metal M source is a water-soluble salt of metal M, preferably at least one of chloride, nitrate, sulfate or acetate; preferably acetate. The present invention shows that the use of a preferred metal acetate raw material can unexpectedly further cooperate with the process, which helps to further improve the performance of the prepared material in oxygen electrocatalysis.
[0014] In the present invention, the metal M includes five or more of the metal elements, and may further be Fe, Co, Ni, Mn and Cu. The present invention shows that the preferred metal combination can further cooperate to further improve the ORR and OER performance of the prepared material.
[0015] The metal chelating agent is a complex capable of coordinating with multiple metals at the same time; preferably, it is at least one of tannic acid and 1,10-phenanthroline; preferably, it is tannic acid.
[0016] Preferably, the mass ratio of the metal M source to the metal chelating agent is 2 to 10:1, and may further be 5 to 10:1.
[0017] In the present invention, the organic complexing agent is a component that can successfully complex with the metal M, for example, it can be a N-containing complexing agent; preferably at least one of dopamine hydrochloride and 2-methylimidazole; preferably dopamine hydrochloride. Studies have shown that the use of a preferred complexing agent, combined with the process of the present invention, can further synergistically regulate the physicochemical characteristics and active sites of the prepared material, and can further synergistically improve the ORR and OER performance of the prepared material.
[0018] Preferably, the mass ratio of the metal M source to the organic complexing agent is 1:0.8-6; further, it can be 1:0.9-4.
[0019] In the present invention, a pH buffer is allowed to be added during the complexation reaction stage.
[0020] Preferably, the pH buffer comprises at least one of tris(hydroxymethyl)aminomethane and tris(hydroxymethyl)methylglycine; preferably tris(hydroxymethyl)aminomethane.
[0021] Preferably, the mass ratio of the metal M source to the pH buffer is 1:0.8-6; further, it can be 1:0.9-4.
[0022] In the present invention, the multi-metal organic complex powder is coated with carbon felt or carbon cloth to obtain a cathode, which can be combined with subsequent implementations to obtain powdered nanocarbon-loaded multi-metal materials, and further to obtain carbon-loaded high-entropy metal materials, and can improve the oxygen electrocatalytic performance of the prepared materials, as well as the electrochemical performance of the assembled battery.
[0023] In the present invention, the graphite sheet is made into the anode, and the multimetallic organic complex powder is wrapped with carbon felt or carbon cloth (preferably carbon felt) to make the cathode. The present invention's research shows that the preferred carbon felt as a packaging material can be combined with the process of the present invention to further optimize the material's physical and chemical structure and further improve the electrochemical performance of the battery.
[0024] In the present invention, the cathode is conductively connected to the negative electrode of the power source, and the anode is conductively connected to the positive electrode of the power source.
[0025] In the present invention, the molten salt includes one or more of NaCl, KCl, LiCl, CaCl2, Na2CO3, K2CO3, and Li2CO3.
[0026] Preferably, the mass ratio of the molten salt to the multimetallic organic complex is 20-80:1; considering the cost, it is further 40-70:1, and further can be 50-65:1.
[0027] In the present invention, a modifying additive is further added to the electrolytic molten system, which includes one or more of LiNO3, Na2SO4, and Na2S2O3; more preferably Na2S2O3. In the present invention, the use of the modifying additive can further enhance the performance of the prepared material; in particular, the preferred modifying additive, combined with the process of the present invention, can obtain better synergy and better OER and ORR performance.
[0028] Preferably, the mass ratio of the molten salt to the modifying additive is 20-80:1; further 40-70:1, and further 55-65:1.
[0029] In the present invention, the electrolysis process requires that when the molten salt reaches the target temperature and enters a molten state, the cathode and the anode are immersed in the molten salt system, and the cathode and the anode are immediately taken out to above the molten salt liquid surface after the power is turned off.
[0030] In the present invention, the electrolysis temperature is 450-750°C, and further 550-650°C.
[0031] Preferably, the electrolysis time is 0.2 to 4 hours, and further can be 0.5 to 1 hour.
[0032] In the present invention, the electrolysis process includes constant voltage electrolysis and / or constant current electrolysis process. Preferably, the constant voltage of the electrolysis process is 0.5-5V, further 1-2.5V; further 1.25-1.75V. The present invention shows that electrolysis at a preferred voltage can be combined with other processes to further synergistically improve the OER, ORR and electrochemical properties of the prepared material.
[0033] The constant current of the electrolysis process is 10~500 mA, further can be 50~300 mA; further can be 80~120mA.
[0034] Preferably, the electrolysis process includes two stages of electrolysis, wherein the first stage of electrolysis is a constant voltage electrolysis process, and the second stage of electrolysis is a constant current electrolysis process. Studies have shown that the use of this preferred process can further regulate the physicochemical characteristics of the prepared material, which can help to further improve the ORR and OER performance of the material.
[0035] Preferably, the first power-on time is 0.2-2 hours, and can be further 0.4-0.6 hours; the second power-on time is 0.2-2 hours, and can be further 0.4-0.6 hours.
[0036] In the present invention, after the electrolysis is completed, the cathode after electrolysis is taken out while it is hot, and then the alloy nanomaterial after electrolysis in the cathode is taken out after cooling. In the present invention, the process described can prepare nano high entropy alloys and can be conducive to preparing materials with uniform distribution of alloy elements.
[0037] In the present invention, the acid solution used in the pickling modification process is an aqueous solution of an inorganic acid; for example, it can be an acid solution of sulfuric acid or hydrochloric acid.
[0038] Preferably, the acid treatment time is 10 to 48 hours.
[0039] In the present invention, the calcination temperature is 700-1000° C., preferably 750-950° C., and further 850-920° C. Under preferred conditions, it can be combined with other processes to further synergistically improve the OER, ORR and electrochemical properties of the prepared material.
[0040] Preferably, the calcination time is 1 to 4 hours, and further can be 2 to 3 hours.
[0041] The present invention also provides a carbon-supported multi-metal electrocatalytic material prepared by the preparation method.
[0042] The preparation method described in the present invention can give the obtained material physicochemical characteristics suitable for oxygen electrocatalysis. For example, a nanoscale alloyed material with highly homogenized elements can be directly obtained, and the material obtained by the preparation method can improve its performance in ORR and OER.
[0043] The present invention also provides an application of the carbon-supported multi-metal electrocatalytic material prepared by the preparation method as a catalytic material for ORR and / or OER.
[0044] In the present invention, the material described in the present invention can be used in any ORR and OER scenarios known in the industry. For example, it can be used as a catalytic material for ORR and / or OER to prepare batteries.
[0045] Preferably, the battery is a metal-air battery, preferably a zinc-air battery.
[0046] The present invention also provides a battery, which comprises the carbon-supported multi-metal electrocatalytic material prepared by the preparation method.
[0047] The battery of the present invention, in addition to comprising the carbon-supported multi-metal electrocatalytic material of the present invention, may have other ingredients, structures and components that are well known.
[0048] Beneficial effects:
[0049] (1) The innovative research of the present invention shows that the multi-metal organic complex powder is wrapped with carbon felt or carbon cloth to form a cathode, and then combined with molten salt electrolysis, acid treatment and subsequent calcination, so that the multi-metal alloy phase separation problem can be solved. In addition, it can also solve the application limitations caused by the existing technology to support the preparation of self-supporting materials. In addition, the research of the present invention shows that the material prepared by the preparation method has excellent OER / ORR activity. In addition, it can also significantly improve the cycle stability of the battery assembled with the obtained material.
[0050] The research of the present invention also shows that it is preferred to use carbon felt as the electrode wrapping material of the metal complex, preferably use Na2S2O3 as the modifying additive, and / or adopt a two-stage electrolysis process of pre-constant voltage and subsequent constant current. This can further achieve synergy, help to further improve the homogenization effect of the prepared nano-alloy material, and help to further improve the OER / ORR activity of the prepared material.
[0051] The carbon-supported multimetal electrocatalyst material of the present invention has excellent oxygen reduction (half-wave potential of 0.86 V) and oxygen evolution (overpotential of 0.18 V) activities. When applied to zinc-air batteries, the open circuit voltage is as high as 1.49 V and the peak power density can reach 255.89 mW cm -2, has excellent charge and discharge stability (can be cycled for 1000h and above).
[0052] (2) The method of the present invention is simple to operate, widely applicable, has controllable preparation conditions, high preparation efficiency, and is easy to realize industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is the XRD pattern of sample 1.
[0054] Figure 2 This is the SEM image of sample 1.
[0055] Figure 3 TEM image of sample 1.
[0056] Figure 4 This is the EDS diagram of sample 1.
[0057] Figure 5 XPS graphs of implementation sample 1 and comparison sample 1.
[0058] Figure 6 This is the ICP-OES statistical bar chart of sample 1.
[0059] Figure 7 This is the SEM image of sample 3.
[0060] Figure 8 This is the TEM image of sample 3.
[0061] Fig. 9 This is the spherical aberration electron microscope image of sample 3.
[0062] Fig.10 This is the EDS diagram of sample 3.
[0063] Fig.11 This is the EDS diagram of comparison sample 8.
[0064] Fig.12 The ORR linear sweep voltammetry curves of some implemented samples and comparative samples are shown in FIG.
[0065] Fig.13 The OER linear sweep voltammograms of some implemented samples and comparative samples.
[0066] Fig.14 The chronoamperometric curves of sample 1 and commercial Pt / C at a constant potential of 0.7 V (vs. RHE).
[0067] Fig.15 For the zinc-air battery assembled with sample 1 and commercial Pt / C and RuO2 at 10 mA cm -2 Discharge capacity diagram at constant current density.
[0068] Fig.16 The zinc-air battery assembled for Example 1 was tested at 10 mA cm -2 Constant current cycle diagram. DETAILED DESCRIPTION
[0069] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0070] The present invention provides an optional method for preparing a carbon-supported multi-metal electrocatalytic material, comprising the following steps:
[0071] Step (1): weigh a certain amount of metal salt and metal chelating agent, dissolve them in deionized water, stir for a certain period of time to carry out metal chelation reaction, then add N-containing complexing agent and pH buffer agent, stir sufficiently to carry out complexation reaction, then centrifuge the solution, and finally dry and grind the centrifuged product to obtain multi-metal organic complex powder;
[0072] Step (2): wrapping the multimetallic organic complex powder obtained in step (1) with carbon felt or carbon cloth to form a cathode, and using a graphite sheet to form an anode;
[0073] Step (3): weigh a certain amount of molten salt components and modifying additives and put them into an alumina crucible, melt them at high temperature in an argon atmosphere in a molten salt electrolytic cell, and after reaching the target temperature, extend the cathode and anode prepared in step (2) below the molten salt liquid surface, apply electricity to react, and then pull them out of the liquid surface after the reaction is completed;
[0074] Step (4): After cooling to room temperature, the electrolysis product in the carbon felt or carbon cloth is taken out, washed with water and modified with acid, then rinsed and filtered with deionized water for multiple times, and then the product on the filter paper is dried.
[0075] Step (5): The product obtained by drying in step (4) is placed in a tubular furnace and calcined again under an argon atmosphere to obtain a carbon-supported multi-metal electrocatalyst material.
[0076] In the present invention, the carbon felt or carbon cloth is a conventional commercial product. For example, as an illustrative solution, in the following case, the carbon felt was purchased from a scientific material station with a thickness of 1 mm, and the carbon cloth was purchased from Changsha Spring.
[0077] The following is a specific implementation plan:
[0078] Example 1
[0079] The method for preparing the carbon-supported multi-metal electrocatalytic material described in this embodiment specifically comprises the following steps:
[0080] Step (1): weigh 1 g of metal acetate (specifically, acetate of Fe, Co, Ni, Cu, and Mn in a molar ratio of 1:1:1:1:1) and dissolve it in 200 mL of deionized water, add 0.1 g of tannic acid thereto, stir for 15 minutes, then add 0.948 g of dopamine hydrochloride and 0.948 g of tris(hydroxymethyl)aminomethane thereto, stir on a magnetic stirring table for 24 hours, centrifuge the solution, and finally place the centrifuged product in a vacuum oven at 60°C and dry for 12 hours, then grind to obtain a multi-metal organic complex powder;
[0081] Step (2): 0.5 g of the multimetallic organic complex powder obtained in step (1) was wrapped with carbon felt to prepare a cathode, and a 1×3 cm graphite sheet was prepared as an anode;
[0082] Step (3): weigh molten salt (13.5 g LiCl, 16.5 g KCl) and a modifying additive (0.5 g LiNO3) into an alumina crucible, and then place it into an electrolytic cell. The cell is sealed and heated to 600°C at a heating rate of 10°C / min in an argon atmosphere. The cathode and anode prepared in step (2) are inserted below the molten salt liquid surface. A constant voltage DC power supply is used to apply a voltage of 1.5 V to the two electrodes. The reaction time is 1 hour. The power is turned off, and then the electrodes are pulled out of the molten salt liquid surface while they are still hot (while the molten salt system is still in a molten state) and allowed to cool naturally.
[0083] Step (4): Take out the sample after the reaction in the carbon felt in step (3), wash away the molten salt component with deionized water, then add 50 mL of 6 mol / L hydrochloric acid solution and stir for 24 hours, then rinse and filter with deionized water for more than 3 times, and finally place the product on the filter paper in a vacuum oven at 60 °C for 12 hours;
[0084] Step (5): The product obtained by drying in step (4) is placed in a tubular furnace, heated to 900°C at a heating rate of 10°C / min in an argon atmosphere and kept at this temperature for 2 hours, and then allowed to cool naturally to obtain a carbon-supported high-entropy nanoalloy electrocatalytic material, which is named as Example 1.
[0085] from Figure 1 From the XRD pattern of sample 1, it can be seen that the diffraction peaks at 43.31°, 50.41° and 74.11° correspond to the (111), (200) and (220) crystal planes of the fcc structure, indicating that the synthesized alloy has a single-phase structure and meets the necessary conditions for high entropy alloys. Figure 2 SEM and Figure 3The TEM image shows that the material is a layered carbon material loaded with metal particles with a particle size of less than 100 nm; Figure 4 The EDS images show that the metals in the material are evenly distributed, and there is no obvious metal phase separation phenomenon, which further proves the synthesis of high entropy nanoalloys. Figure 5 From the XPS images, it can be seen that sample 1 contains five metals, namely, Fe, Co, Ni, Cu, and Mn. Compared with sample 1, the valence state of cobalt is increased, which indicates that the other added metals interact with cobalt, which may cause its adsorption energy to change, which is conducive to adjusting to the appropriate oxygen electrocatalytic adsorption energy. Figure 6 The ICP-OES results show that the contents of various metals in the material are similar, consistent with the input metal ratio, and meet the definition of high entropy alloys.
[0086] Example 2
[0087] Compared with Example 1, the only difference is that two stages of power-on treatment are performed in step (3), wherein the first stage of power-on voltage is 1.5 V constant voltage, the power-on time is 0.5 h, and the second stage of power-on current is 100 mA constant current, the power-on time is 0.5 h, and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 2.
[0088] Example 3
[0089] Compared with Example 1, the only difference is that the 1 g of metal salt in step (1) is changed to 0.25 g, and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 3. Figure 7 and Figure 8 It can be seen from the electron microscope image that sample 3 is a lamellar material; Fig. 9 This indicates that the metal is loaded on the surface of the material in the form of single atoms. Fig.10 The EDS images show that the metal is evenly dispersed and can be classified as a carbon-supported high-entropy single-atom material.
[0090] Example 4
[0091] Compared with Example 1, the only difference is that the molten salt in step (3) is replaced by 30 g Na2CO3, and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 4.
[0092] Example 5
[0093] Compared with Example 1, the only difference is that the modifying additive in step (3) is replaced by Na2S2O3, and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 5.
[0094] Example 6
[0095] Compared with Example 1, the only difference is that the holding temperature in step (3) is changed to 700° C., the power-on voltage is changed to 2.0 V, and the power-on time is changed to 2 h. Other operations and parameters are the same as those in Example 1. The prepared sample is named Example 6.
[0096] Example 7
[0097] Compared with Example 1, the only difference is that the metal acetates of Fe, Co, Ni, Cu, and Mn in step (1) are replaced with equal masses of chloroplatinic acid, palladium chloride, and ruthenium trichloride (the molar ratio of platinum, palladium, and ruthenium is 1:1:1), and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 7.
[0098] Example 8
[0099] Compared with Example 1, the only difference is that the carbon felt in step (2) is replaced by carbon cloth, and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 8.
[0100] Example 9
[0101] Compared with Example 1, the only difference is that the calcination temperature in step (5) is changed to 800°C and the time is 3 hours, and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 9.
[0102] Example 10
[0103] Compared with Example 1, the only difference is that in step (3), no modifying additive is added, and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 10.
[0104] Embodiment 11
[0105] Compared with Example 1, the only difference is that the constant voltage in step (3) is changed to a constant current electrolysis of 100 mA, and the other operations and parameters are the same as those in Example 1. The prepared sample is named Example 11.
[0106] Comparative Example 1
[0107] Compared with Example 1, the only difference is that in step (1), the metal acetate is changed to single cobalt acetate, and the other operations and parameters are the same as those in Example 1. The prepared sample is named comparative sample 1. Figure 5 It can be seen from the XPS graph that the valence state of cobalt in comparative sample 1 is reduced.
[0108] Comparative Example 2
[0109] Compared with Example 1, the only difference is that no metal salt component is added in step (1), and other operations and parameters are the same as those in Example 1. The prepared sample is named comparative sample 2.
[0110] Comparative Example 3
[0111] Compared with Example 1, the only difference is that the positive and negative electrodes in step (2) are exchanged (ie, the carbon felt is used as the anode and the graphite sheet is used as the cathode), and the other operations and parameters are the same as those in Example 1. The prepared sample is named comparative sample 3.
[0112] Comparative Example 4
[0113] Compared with Example 1, the only difference is that the chelation and complexation process in step (1) is not performed, but the solid phases of the raw materials for synthesizing the metal complex are physically mixed, and the physical solid phase mixture directly replaces the multi-metal organic complex powder in step (2), and step (2) and subsequent treatment are performed. Other operations and parameters are the same as those in Example 1. The prepared sample is named comparative sample 4.
[0114] Comparative Example 5
[0115] Compared with Example 1, the only difference is that in step (3), no voltage is applied to the two electrodes (that is, the molten salt pyrolysis scheme), and the other operations and parameters are the same as those in Example 1. The prepared sample is named Comparative Sample 5.
[0116] Comparative Example 6
[0117] Compared with Example 1, the only difference is that the acid treatment in step (4) is changed to 6 mol / L KOH solution treatment, and the other operations and parameters are the same as those in Example 1. The prepared sample is named comparative sample 6.
[0118] Comparative Example 7
[0119] Compared with Example 1, the only difference is that step (5) is not performed, and other operations and parameters are the same as those of Example 1. The prepared sample is named comparative sample 7.
[0120] Comparison sample 8
[0121] Compared with Example 1, the only difference is that in step (1), no metal chelating agent is added, and the other operations and parameters are the same as those in Example 1. The prepared sample is named comparative sample 8. Fig.11 The EDS images show that the metal phase separation occurred in the sample without the addition of metal chelating agent, and the metal particle size was uneven.
[0122] Test example
[0123] Test samples: all implementation samples and comparative samples; commercial Pt / C catalyst (20 wt.%, Hesen); commercial RuO2 catalyst (analytical grade, MacLean).
[0124] Test method:
[0125] (1) Preparation of working electrode: Take 4 mg of catalyst sample, add 800 µL of alcohol and 170 µL of deionized water, and ultrasonically disperse for 15 min. Then add 30 µL of 5 wt.% Nafion solution and continue ultrasonicating for 15 min to obtain a uniform catalyst ink. 10 µL of the prepared catalyst ink is evenly dropped onto the glassy carbon surface of the rotating disk electrode and allowed to air dry naturally.
[0126] (2) Oxygen electrocatalytic performance test: The oxygen electrocatalytic performance of the catalyst was tested using a standard three-electrode electrochemical workstation (Gamry). The rotating disk electrode loaded with the catalyst was the working electrode, the platinum ring electrode was the counter electrode, and the Hg / HgO electrode was the reference electrode. For the test, the specific operating conditions were that high-purity oxygen was passed into the electrolyte for 30 minutes before the electrochemical test to allow the electrolyte to reach oxygen saturation. For the oxygen reduction reaction (ORR) performance, the electrolyte was a 0.1 mol / L KOH solution, and the linear sweep voltammetry (LSV) was measured at a scan rate of 5 mV / s in the voltage range of 0.2 to -0.8 V, with the scan direction being negative; the stability was obtained using the chronoamperometry at 0.7 V (vs. RHE). For the oxygen evolution reaction (OER) performance, the electrolyte was 1 mol / L KOH solution, and the linear sweep voltammetry (LSV) was measured at a scan rate of 5 mV / s in the voltage range of 0.2 to 1.1 V, and the scan direction was forward scan. The results of oxygen electrocatalytic performance are shown in Tables 1 and 2.
[0127] (3) Zinc-air battery assembly: zinc plate as negative electrode, thickness 0.5 mm, reaction area 4.5 cm 2 ; The nickel foam, air diffusion layer and carbon paper were hot pressed together, and the catalyst ink prepared in step (1) was drop-coated on the surface of the carbon paper as the positive electrode. The catalyst loading was controlled at 1 mg cm -2 The reaction area is 1 cm 2 ; The electrolyte is a mixed solution of 6 mol / L KOH and 0.2 mol / LZn(CH3COO)2, and a pump is used to circulate the electrolyte.
[0128] (4) Zinc-air battery performance test: The polarization curve was measured on a Gamry electrochemical workstation at a scan rate of 5 mV / s in the voltage range of 0.5~2.5 V. The performance of the assembled zinc-air battery was evaluated using a blue electric test system. The cycle life of the homemade zinc-air battery was estimated by using a constant current charge and discharge process with a cycle time of 20 minutes (charging for 10 minutes and discharging for 10 minutes). The constant current discharge process obtained the zinc-air battery in the range of 1~150 mA cm -2 The discharge platform at different current densities; According to the constant current density of 10 mA cm-2 The specific capacity of the zinc-air battery was calculated based on the constant current discharge curve and the consumed mass of the zinc sheet. The performance results of the zinc-air batteries assembled from different samples are shown in Tables 3 and 4.
[0129]
[0130]
[0131]
[0132]
[0133] From Table 1 and Table 2 and Fig.12 and Fig.13 It can be seen that compared with comparative sample 1, comparative sample 2 and commercial Pt / C+RuO2, implementation sample 1 has a higher ORR half-wave potential (0.84 V) and a lower OER overpotential (0.20 V), which is better than commercial Pt / C (half-wave potential 0.83 V) and RuO2 (overpotential 0.30 V) catalysts. Fig.14 The ORR stability of Example 1 is higher than that of the commercial Pt / C catalyst. At the same current density, compared with the commercial Pt / C and RuO2 catalysts, Example 1 shows a smaller charge-discharge voltage gap, which indicates that the electrocatalytic activity of Example 1 is improved, thereby accelerating the reaction kinetics. In addition, it can be seen from Tables 3 and 4 that the zinc-air battery using the electrocatalyst of Example 1 achieves 253.76 mWcm -2 The peak power density exceeds that of commercial Pt / C and RuO2 catalysts; from Tables 3 and 4 and Fig.15 It can be seen that the discharge capacity of the zinc-air battery using the electrocatalyst of Example 1 is higher than that of the commercial Pt / C and RuO2 catalysts; Fig.16 It can be seen that the electrocatalyst of Example 1 has a -2 It exhibits excellent cycling stability at current densities of 2.5 and 1.5 % and the energy efficiency decay is still negligible after cycling for more than 1000 h.
[0134] In addition, it can be seen from the examples and comparative examples that the multi-metal organic complex powder is wrapped with carbon felt or carbon cloth to form a cathode, and then combined with molten salt electrolysis, acid treatment and subsequent calcination, so that the multi-metal alloy phase separation problem can be solved. In addition, it can also solve the application limitations caused by the existing technology to support the preparation of self-supporting materials. In addition, the present invention shows that the material prepared by the preparation method has excellent OER / ORR activity, and in addition, it can significantly improve the cycle stability of the battery assembled with the prepared material.
[0135] In addition, it can be seen from Examples 1 / 2 and 11 that the two-stage electrolysis process of pre-constant voltage followed by constant current of the present invention can unexpectedly further improve the ORR and OER performance of the prepared material. It can be seen from Examples 1 / 5 and 10 that adding a modifier to the molten salt system, especially using Na2S2O3 as a modifier, can unexpectedly further optimize the morphology of the prepared nano-alloy particles and the element homogenization distribution effect, which helps to further improve the OER / ORR and battery performance of the prepared material.
[0136] It can also be known from Examples 1 and 8 that using carbon felt to wrap the metal complex for molten salt electrolysis can unexpectedly further optimize the morphology of the prepared nano-alloy particles and the element homogenization distribution effect, which helps to further improve the OER / ORR and battery performance of the prepared material.
Claims
1. A method for preparing a carbon-supported multi-metal electrocatalytic material, characterized in that: The multi-metal organic complex is wrapped with carbon felt or carbon cloth to form a cathode, which is conductively connected to an anode and electrolyzed in a molten salt system. After the electrolysis is completed, the electrolysis product in the carbon felt or carbon cloth is taken out and washed with water, acid washed and calcined in sequence to obtain a nano-scale carbon-supported multi-metal electrocatalyst material; The multi-metal organic complex is a complex formed by a metal M source, a metal chelating agent and an organic complexing agent, and the metal M comprises three or more of Fe, Co, Ni, Cr, Mn, Cu, V, Mo, Ti, Au, Ag, Pt, Pd, Ru, Ir, Rh, W, La, Cd, Zr, Ga, In and Sn.
2. The preparation method according to claim 1, characterized in that The preparation steps of the multi-metal organic complex are: pre-chelating the metal M source and the metal chelating agent, and then performing a complexing reaction with the organic complexing agent to obtain; The metal chelating agent is a complex that can coordinate with multiple metals at the same time; The metal M source is a water-soluble salt of metal M; The metal M comprises five or more of the metal elements; The mass ratio of metal M source to metal chelating agent is 2-10:1; The organic complexing agent is a N-containing complexing agent; The mass ratio of the metal M source to the organic complexing agent is 1:0.8~6.
3. The preparation method according to claim 2, characterized in that: A pH buffer is added during the complexation reaction stage; The pH buffer comprises at least one of tris(hydroxymethyl)aminomethane and tris(hydroxymethyl)methylglycine; The mass ratio of the metal M source to the pH buffer is 1:0.8-6.
4. The preparation method according to claim 1, characterized in that: The molten salt includes one or more of NaCl, KCl, LiCl, CaCl2, Na2CO3, K2CO3, and Li2CO3; The mass ratio in molten salt and multimetallic organic complex is 20~80:1; A modifying additive is also added to the electrolytic molten system, which includes one or more of LiNO3, Na2SO4, and Na2S2O3; The mass ratio of molten salt to modified additive is 20~80:1; The temperature of the molten salt system during the electrolysis stage is 450~750℃; The electrolysis time is 0.2~4h.
5. The preparation method according to claim 1, characterized in that: The electrolysis process includes constant voltage electrolysis and / or constant current electrolysis process, wherein the constant voltage is 0.5-5 V; the constant current is 10-500 mA.
6. The preparation method according to claim 5, characterized in that: The electrolysis process includes two stages of electrolysis with power on, wherein the first stage of electrolysis with power on is a constant voltage electrolysis process, and the second stage of electrolysis with power on is a constant current electrolysis process.
7. The preparation method according to claim 1, characterized in that: The acid solution used in the pickling modification process is an aqueous solution of an inorganic acid; Acid treatment time is 10~48h; Calcination temperature is 700~1000℃; The calcination time is 1~4h.
8. A carbon-supported multi-metal electrocatalytic material prepared by the preparation method according to any one of claims 1 to 7.
9. An application of a carbon-supported multi-metal electrocatalytic material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It can be used as a catalytic material for ORR and / or OER.
10. A battery, characterized in that: A carbon-supported multi-metal electrocatalytic material prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Nano high-entropy alloy electro-catalytic material, preparation thereof and application of nano high-entropy alloy electro-catalytic material in OER / ORR
CN118699383A
Atomic-level controllable high-entropy catalyst as well as preparation method and application thereof
CN118847148A
KR20220094950A